Industry profesional talk program (Oct 2021 - Feb2022) Infrastructure Design Project (IDP) / Mohamad Zain Hashim and Muriatul Khusmah Musa - Hashim, Mohamad Zain; Musa, Muriatul Khusmah (Unit Penerbitan FKAPP, 2022)
The purpose of this professional talk program was to meet the course requirements for Infrastructure Design Project (IDP) CEC 594. The program's goals were to: i) provide students with practical knowledge of civil engineering and construction consulting work in industry ii) foster a culture of continuous learning iii) provide early input and enthusiasm for innovation to students, and iv) strengthen student-industry relationships. Students were required to attend each talk and submit a brief report about it. The programme has managed to achieve the following learning outcomes: 1. Introduced students to some of the stakeholders and major players in the construction industry. 2. Exposed students to common civil engineering products and practices in the industry. 3 Exposed students to design requirements in the field of civil engineering. 4. Encouraged continuous learning in students to enable them to keep abreast of current developments in the industry.